Can the EMS be Exported? Lessons from Ten Years of Monetary Policy Coordination in Europe - Francesco Giavazzi; Alberto Giovannini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1989)
The paper is organized around two main questions. The first is, why is the eversion to exchange rate fluctuations stronger in Europe than elsewhere? the second question is: how does the EMS hold together?
Keywords: 330